Praktik Ibadah Tanpa Speaker: Studi Living Hadis di Masjid Al-Huda Desa Kayu Agung: The Practice of Worship Without Loudspeakers: A Living Hadith Study at Al-Huda Mosque, Kayu Agung Village - Abil Ash; Ahmad Jamil; Muhammad Awfa Munawar; Jaya Rukmana (Al-Ma‘ani: Journal of Islamic Studies, 2026)
This study examines the hadith-based understanding that forms the foundation for the practice of worship without loudspeakers at Jami’ Al-Huda Mosque in Kayu Agung Village, Sepatan District, Tangerang Regency. In the context of modern society where sound amplification technology is commonly integrated into religious practices, the policy of Al-Huda Mosque which has not used loudspeakers since its establishment around 1951 constitutes a distinctive phenomenon worthy of in-depth scholarly investigation. This research employs a descriptive qualitative approach using a case study method and the Living Hadith framework. Data were collected through direct observation, in-depth interviews with mosque administrators, religious figures, and congregants, as well as documentary analysis of primary hadith sources. The findings indicate that the interpretation of hadiths concerning tranquility in worship particularly the hadith prohibiting disturbance to fellow worshippers from Imam Malik (al-Muwaṯṯa’ no. 177) and Abū Dāwūd (Sunan no. 1332) is significantly shaped by local traditions, the religious perspectives of community leaders, and a collective desire to maintain solemnity without disturbing the surrounding environment. Although the hadiths do not explicitly prohibit the use of loudspeakers, congregants interpret them as guidance to uphold tranquility and avoid mutual disturbance during worship. The speakerless worship practice at Al-Huda Mosque represents a contextual interpretation of hadiths reflecting local values of serenity, etiquette, and social harmony.